PENGARUH BRAND AMBASSADOR KOREA LEE MINHO, KUALITAS PRODUK, DAN PERSEPSI HARGA TERHADAP KEPUTUSAN PEMBELIAN SUNSCREEN AZARINE (STUDI PADA MAHASISWA AKTIF FAKULTAS EKONOMIKA DAN BISNIS UNESA) - Anisa Tri Lestari; Septyan Budy Cahya (Jurnal Pendidikan Tata Niaga (JPTN), 2023)
In the era of globalization, all information is easily obtained by people worldwide, which can lead to global cultural exchange. One of the cultural exchanges that occurred in Indonesian society was the inclusion of South Korean culture. South Korea is famous for its beauty standards which have influenced the high interest in treating facial skin in Indonesia, which is marked by the increasing income of beauty products in Indonesia. The entry of South Korean culture is used by the company as a marketing strategy by using Korean artist brand ambassadors to influence purchasing decisions. In addition, companies compete to improve product quality and determine pricing strategies to influence consumers' purchasing decisions. This study aims to analyze the influence of Korean brand ambassador Lee Minho, product quality, and price perceptions on the purchase decision of Azarine sunscreen. The population in this study were students of the Unesa Faculty of Economics and Business who had purchased Azarine sunscreen products with a sample of 98 students using the Slovin method. The sampling technique used a purposive sampling method and data collection through online questionnaires. The data analysis technique used multiple linear regression analysis which was processed with SPSS 25 software. The results showed that the brand ambassador variable partially affected purchasing decisions. The product quality variable has a partial effect on purchasing decisions. The price perception variable has a partial effect on purchasing decisions. As well as Korean brand ambassador Lee Minho, product quality and price perceptions simultaneously influence the decision to buy Azarine sunscreen.